Upaya Meningkatkan Hasil Belajar Siswa dengan Metode Iqro’ pada Mata Pelajaran BTA di SD Negeri 2 Lumbungkerep Wonosari Ta.2021/2022 - Nita Nur Samsiyah; Uswatun Khasanah; M. Fatchurrohman (Journal on Education, 2023)
Based on the results of research observations, in the odd semester learning outcomes for BTA subjects in 2021/2022, there are some students who have not completed due to variations in teaching styles that do not support student activity in the learning process that still uses the old learning method. From this, the formulation of the problem in th is study is: "Is the application of the Iqro 'Method able to improve student learning outcomes in BTA subjects at SD Negeri 2 Lumbungkerep Wonosari TA.2021/2022?".Referring to the problems mentioned above, the authors try to improve student learning outcomes by using the Iqro 'method on each sub-subject of BTA subjects. In the learning process students will be directly involved in learning activities. This research is in the form of classroom action research for two cycles, and in each cycle there are two meetings with each meeting is 2x35 minutes, then the stages are planning, implementation, observation and reflection.The purpose of this study is to improve student learning outcomes with the Iqro 'method on BTA subjects, students who have participated in learning using the Iqro' method for third grade students of SD Negeri 2 Lumbungkerep Wonosari TA.2021/2022. The data collection technique used in this research is to use learning outcomes tests, observation and documentation.Based on the results of class action research and the discussion that has been stated, it can be concluded as follows: learning using the application of the iqro' method can improve student learning outcomes in the first cycle with 75.08% completeness and in the second cycle 87.08%. This means that there is an increase from cycle I to cycle II as much as 21.70%.